Pedigree analysis of diabetes mellitus in Minangkabau ethnic - S. Syamsurizal; Siti Halifah; Elsa Badriyya (Genetikawan Muda Indonesia, 2021)
Diabetes mellitus has a tendency to be inherited. The inheritance pattern of diabetes mellitus in the Minangkabau ethnic group follows the mitochondrial and autosomal inheritance pattern. Patients with diabetes mellitus in the Minangkabau ethnicity have a equal distribution between men and women. Patients with diabetes mellitus in this ethnic group generally know that they suffer from diabetes mellitus in old age or after other complications arise due to diabetes mellitus.